Fatores determinantes da direção da estratégia de diversificação de grupos empresariais: teoria e evidências do Brasil - Vallandro, Luiz Felipe Jostmeier (Universidade do Vale do Rio dos Sinos, 2016)
This study investigated the determinants of the direction of diversification strategy of business groups in Brazil. Using both transaction costs theory (WILLIAMSON, 1975; 1979; 1985) and agency theory (JENSEN & MECKLING, 1976) as theoretical pillars, this study aimed to analyze the influence of a set of factors on the choice of the direction of diversification strategy of Brazilian business groups, that occurs towards related or unrelated businesses (related vs. unrelated diversification, respectively) to the main activity of the group. The empirical strategy considered a sample of 51 business groups identified among the 200 largest business groups in Brazil between 2009 and 2014, according to the publication of the yearbook Valor Grandes Grupos. The direction of diversification took the form of a binary variable, with the value of one for unrelated diversification, and zero for related diversification. The variables used as the determinants of the direction of diversification were: profitability, debt, capex, risk, physical assets, intangible assets, ownership structure considering only one shareholder holding at least 50% +1 of the shares with voting rights (Definido1), ownership structure formed by a group of shareholders sharing the control (Definido2), and family control. Two control variables were set: size and growth opportunities. Pooled probit panel regressions were used to run the empirical tests. The evidence suggest that a set of factors influences the direction of diversification strategy pursued by Brazilian business groups. The main conclusion is that factors like debt, risk, capex, and ownership structure formed by a group of shareholders sharing the control of the business group influence positively the probability of the choice of unrelated diversification. On the other hand, factors like intangible assets and ownership structure considering only one shareholder holding at least 50% +1 of the shares with voting rights influence negatively the probability of the choice of unrelated diversification.
Keywords: Estratégia de diversificação; Direção da diversificação; Diversificação relacionada; Diversificação não-relacionada; Fatores determinantes; Grupos empresariais; Economias emergentes; Diversification strategy; Direction of diversification; Related diversification; Unrelated diversification; Determinant factors; Business groups; Emerging economies; ACCNPQ::Ciências Sociais Aplicadas::Administração